Using a 2-Stage Strategy with Respondent-Driven Sampling to Recruit a Hard-to-Reach Population for a Placebo Microbicide Gel Clinical Trial in Nellore, Andhra Pradesh (India) - Tun, Waimar; Katzen, Lauren L.; Abbott, Sharon A.; Srikrishnan, Aylur K.; Kelly, Christine A.; Sarna, Avina; Friedland, Barbara A.; Solomon, Suniti; Mensch, Barbara S. (AIDS and behavior, 2015)
Traditional recruitment methods for microbicide efficacy trials are labor intensive and may fail to reach high-risk hard-to-reach populations. We report duration of recruitment and lessons learned from a two-stage process to recruit female sex workers (FSWs) into a placebo microbicide trial, and examined characteristics associated with successful recruitment of peers who screened for and enrolled in the trial. FSWs were first recruited via respondent-driven sampling (RDS) to complete a survey and subsequently invited to screen for enrollment into a placebo microbicide trial taking place at a local clinic. It took 6 months to enroll 267 participants into the trial. Successful recruiters of peers who enrolled were more likely to have enrolled themselves (AOR 2.0, CI 1.3–2.9) and less likely to visit Nellore city (AOR 0.5, CI 0.3–0.9). Recruitment of FSWs via a two-stage recruitment strategy with RDS can be a good option for future clinical trials.